2017
DOI: 10.3233/ch-179227
|View full text |Cite
|
Sign up to set email alerts
|

Breast sensitivity after mastectomy and autologous reconstruction

Abstract: The skin sparing mastectomy combined with immediate reconstruction by DIEAP-flap provides an excellent therapeutic option for patients, who are suitable for this technique, which takes into account not only the form but also the sensitivity of the breast.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…. Women who are undergoing or underwent mastectomy with immediate reconstruction, with either tissue expander (TE) or neurotized DIEP flap, were prospectively identified and consented at their preoperative or postoperative visit at predetermined time points (3,6,9,12,18, and 24 or more months postoperatively) from April 2019 to April 2021. Exclusion criteria included diabetic neuropathy, chemotherapy-induced neuropathy, and other causes of peripheral neuropathy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…. Women who are undergoing or underwent mastectomy with immediate reconstruction, with either tissue expander (TE) or neurotized DIEP flap, were prospectively identified and consented at their preoperative or postoperative visit at predetermined time points (3,6,9,12,18, and 24 or more months postoperatively) from April 2019 to April 2021. Exclusion criteria included diabetic neuropathy, chemotherapy-induced neuropathy, and other causes of peripheral neuropathy.…”
Section: Methodsmentioning
confidence: 99%
“…Although the decision to proceed with one reconstructive option over others is personalized and multifactorial, restoration of breast sensation has become increasingly important to patients in their decision making 10 . Despite the increasing importance, literature in sensory return has lagged behind, focusing largely on single reconstructive modalities compared with mastectomy alone 11–13 . Magarakis et al, 14 in one of the few studies that compared alloplastic with autologous reconstruction, found that irradiated deep inferior epigastric perforator (DIEP) flap skin is associated with better sensory recovery than irradiated skin over implants.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] In terms of treatment, around 40% of breast tumours need to be treated by removal of the entire breast (mastectomy) and many of these women perceive this therapeutic procedure to be sufficiently traumatic to request reconstruction. [7][8][9] Since breast cancer has a high survival rate and today post-mastectomy breast reconstruction constitutes a well-established component of breast cancer treatment, it is evident that improving reconstruction outcomes is an important on-going oncological goal. 8 The key element of these outcomes is symmetry with the opposite breast and surgeons aim to achieve this objective principally by approximating the dimensions of the reconstructed breast to those of the mastectomy specimen.…”
Section: Introductionmentioning
confidence: 99%
“…The results, published in 2020, showed one flap loss in 44 autologous reconstructions [2]. In another study, we compared two distinct mastectomy techniques followed by autologous reconstruction with regard to breast sensitivity [3].…”
mentioning
confidence: 99%